The Robot-Assisted Extravesical Anti-reflux Surgery: How We Overcame the Learning Curve - Sahadev, Ravindra; Spencer, Katelyn; Srinivasan, Arun K.; Long, Christopher J.; Shukla, Aseem Ravindra (Frontiers in Pediatrics, 2019)
Management of vesicoureteral reflux (VUR) has evolved over the past several decades, with a trend towards a decrease in surgical management. In spite of this, ureteral reimplantation remains a commonly performed procedure for pediatric urologists in selected cases. Although the basic tenets of the ureteral reimplant procedure remain the same, the extra- vs intravesical approach, and the traditional open vs minimally invasive approach remain the primary options to correct reflux. Considering the advantages conferred by the robotic surgery platform, many leading centers have preferentially adopted robot-assisted laparoscopic extravesical anti-reflux surgery, or in common surgical parlance, the robot-assisted laparoscopic ureteral reimplantation (RALUR), over pure laparoscopic or open approaches. Predicated on our experience of performing over 170 cases of RALUR, we have made technical modifications which we posit reduce the morbidity of the procedure while offering acceptable outcomes. This review highlights the evolution and establishment of RALUR as a standardization of care in the surgical management of VUR at our institution. In particular, we emphasize the technical nuances and specific challenges encountered through the learning curve in hopes of facilitating this process for others.